Improved Myocardial Function in Autoimmune-Mediated Fetal Complete Atrioventricular Block Following Dexamethasone and Intravenous Immunoglobulin: A Case Report - Maria Elisa Martini Albrecht; Milena Giuberti Bathomarco; Gustavo Yano Callado; Nathalie Jeanne Bravo-Valenzuela; Edward Araujo Júnior (Women)
This case report describes a fetus diagnosed with complete atrioventricular block (CAVB) associated with positive maternal anti-Ro and anti-La antibodies, referred to our fetal cardiology unit at 25 weeks of gestation. The diagnosis of systemic lupus erythematosus (SLE) was established during the investigation of the fetal condition. Oral dexamethasone was initiated and well tolerated, with no adverse effects reported throughout the remainder of the pregnancy. The fetal heart rate (HR) remained above 50 bpm, and, therefore, no beta-sympathomimetic agents were administered. Due to progressive reduction in myocardial contractility and the appearance of early signs of endocardial fibroelastosis, intravenous immunoglobulin (IVIG) therapy was initiated. The patient was hospitalized for the infusion, which was well tolerated without complications, and a second IVIG cycle was administered four weeks later. Significant improvement in ventricular contractility and reduction in fibroelastosis were observed. As reported in the literature, no chronotropic effect was noted, and fetal HR remained stable after treatment. Weekly monitoring of cardiovascular profile score and fetal HR was maintained, with the score consistently remaining at 8 throughout gestation, supporting continued outpatient management. Delivery occurred at 36 weeks and 3 days due to spontaneous preterm labor. A male neonate weighing 3025 g was delivered with Apgar scores of 8 and 9, and an initial heart rate of 84 bpm. Neonatal electrocardiography confirmed persistent CAVB, and the newborn was monitored in the neonatal intensive care unit. At follow-up, the infant remains clinically stable and has not required permanent pacemaker implantation.